Cost Effectiveness of Bevacizumab Plus Chemotherapy for the Treatment of Advanced and Metastatic Cervical Cancer in India—A Model-Based Economic Analysis. (14th March 2022) - Gupta, Nidhi; Nehra, Prerika; Chauhan, Akashdeep Singh; Mehra, Nikita; Singh, Ashish; Krishnamurthy, Manjunath Nookala; Rajsekhar, Kavitha; Kalaiyarasi, Jayachandran Perumal; Roy, Partha Sarathi; Malik, Prabhat Singh; Mathew, Anisha; Malhotra, Pankaj; et al.
Abstract : PURPOSE: Patients with advanced and metastatic cervical cancer have a poor prognosis with a 1-year survival rate of 10%-15%. Recently, an antiangiogenic humanized monoclonal antibody bevacizumab has shown to improve the survival of these patients. This study was designed to assess the cost effectiveness of incorporating bevacizumab with standard chemotherapy for the treatment of patients with advanced and metastatic cervical cancer in India. METHODS: Using a disaggregated societal perspective and lifetime horizon, a Markov model was developed for estimating the costs and health outcomes in a hypothetical cohort of 1, 000 patients with advanced and metastatic cervical cancer treated with either standard chemotherapy alone or in combination with bevacizumab. Effectiveness data for each of the treatment regimen were assessed using estimates from Gynecologic Oncology Group 240 trial. Data on disease-specific mortality in metastatic cervical cancer, health system cost, and out-of-pocket expenditure were derived from Indian literature. Multivariable probabilistic sensitivity analysis was undertaken to account for parameter uncertainty. RESULTS: Over the lifetime of one patient with advanced and metastatic cervical cancer, bevacizumab along with standard chemotherapy results in a gain of 0.275 (0.052-0.469) life-years (LY) and 0.129 (0.032-0.218) quality-adjusted life-years (QALY), at an additional cost of $3, 816 US dollars (USD; 2, 513-5, 571) compared with standard chemotherapy alone. This resulted in an incremental cost of $19, 080 USD (7, 230-52, 434) per LY gained and $34, 744 USD (15, 782-94, 914) per QALY gained with the use of bevacizumab plus standard chemotherapy. CONCLUSION: Addition of bevacizumab to the standard chemotherapy is not cost effective for the treatment of advanced and metastatic cervical cancer in India at a threshold of 1-time per-capita gross domestic product.